Association of Bone Density Monitoring in Routine Clinical Practice With Anti‐Osteoporosis Medication Use and Incident Fractures: A Matched Cohort Study. (7th August 2019) - Leslie, William D; Morin, Suzanne N; Martineau, Patrick; Bryanton, Mark; Lix, Lisa M
ABSTRACT: Routine bone mineral density (BMD) monitoring of individuals during the initial 5 years of anti‐osteoporosis treatment is controversial. Using a registry‐based cohort from the Province of Manitoba, Canada, we compared anti‐osteoporosis medication use and fracture outcomes in women with versus without BMD monitoring receiving anti‐osteoporosis medication. We identified 4559 women aged 40 years and older receiving anti‐osteoporosis therapy with serial BMD testing (monitoring) within 5 years (mean interval 3.2 years) and 4559 propensity score–matched women without BMD monitoring. We assessed anti‐osteoporosis medication use over 5 years from a population‐based retail pharmacy database. Incident fractures to 10 years from health services data. During median 10 years observation, 1225 (13.4%) women developed major osteoporotic fracture, including 382 (4.2%) with hip fractures. Monitored women had significantly better fracture‐free survival for major osteoporotic fracture ( p  = 0.040; 10‐year cumulative risk 1.9% lower, 95% confidence interval [CI] 0.3–3.6%) and hip fracture ( p  = 0.001; 10‐year cumulative risk 1.8% lower, 95% CI 0.7–2.8%) compared with women who were not monitored. Hazard ratios (HRs) were significantly lower in monitored versus not monitored women for major osteoporotic fracture (HR = 0.89, 95% CI 0.80–0.98) and hip fracture (HR = 0.74, 95% CI 0.63–0.87). Days of medication use, medication persistence ratio, and treatment switching over 5 years were greater in monitored versus not monitored women. At the end of 5 years, more women in the monitored group persisted on treatment and more switched treatment, with switching behavior associated with an observed interval reduction in BMD. In conclusion, our findings suggest a possible role for BMD monitoring after initiating anti‐osteoporosis therapy in the routine clinical practice setting. © 2019 American Society for Bone and Mineral Research.